Phenotyping juvenile myoclonic epilepsy. Praxis induction as a biomarker of unfavorable prognosis. (November 2015) - Uchida, Carina Gonçalves Pedroso; de Carvalho, Kelly Cristina; Guaranha, Mirian Salvadori Bittar; Guilhoto, Laura Maria Figueiredo F.; de Araújo Filho, Gerardo Maria; Wolf, Peter; Yacubian, Elza Márcia Targas
Highlights: There is a male preponderance in juvenile myoclonic epilepsy patients with praxis induction. Praxis induction is related to focal epileptiform discharges. Praxis induction is related to loss of the characteristic chronodependency of juvenile myoclonic epilepsy and with reduced response to antiepileptic drugs. Abstract: Purpose: Juvenile myoclonic epilepsy (JME) is a heterogeneous syndrome with seizures presenting typical fluctuation in diurnal cycle and relation with awakening. Few publications have approached clinical expressions of praxis induction (PI) in the nosology of JME as well as its impact on outcome. The aim of this study is to characterize PI as the only reflex trait in JME and its relation with prognosis. Method: JME with PI reported on a questionnaire and confirmed by video-EEG testing (Group 1, 20 patients) were compared with JME without any reflex epileptic trait (Group 2, 25 patients) and followed for a mean of 7.82 years (SD = 3.98). Circadian distribution and frequency of seizures were assessed in a diary. Patients also had psychiatric evaluation. Results: Prevalence of PI was 20/133 (15%) JME patients, and was predominant in males (1.5 male: 1 female; OR 13; p = 0.042). Among Group 1 patients, only 2/20 presented seizures exclusively in the morning ( p = 0.013), and none, exclusively on awakening ( p < 0.001). PI patients had worse prognosis regarding control of myocloni ( p = 0.02) and absences ( p = 0.01); only 7/20 (35.0%) could be treated with VPA in monotherapy ( p = 0.01). At the last follow-up, 2/20 (10.0%) of Group 1 and 10 (40.0%) of Group 2 patients were free of all three seizure types ( p = 0.02). Even though relative risk of stress as a precipitant of seizures increased 3.82 times in Group 1, psychiatric comorbidities were not different between groups. Conclusion: PI reflex trait in JME is related to seizures without preferential circadian occurrence and reduced response to antiepileptic drugs.